2015
DOI: 10.3102/0002831215587352
|View full text |Cite
|
Sign up to set email alerts
|

Early Career Outcomes for the “Best and the Brightest”

Abstract: Educational efforts aimed at attracting the ''best and brightest'' into the teaching profession are widespread and include national programs, such as Teach for America and the New Teacher Project Teaching Fellows, as well as regional and state-based programs, city-based programs, and university-based programs. Yet, studies of attrition in programs aimed at recruiting highly selective teachers provide some evidence that highly selective entrants are less likely to persist in a teaching career. Using data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 68 publications
0
24
0
9
Order By: Relevance
“…There is a strong influence on the decision to retire from the work attitudes of the worker; those he or she possesses towards retirement and the norms at the workplace (including perceived social pressure for retirement). Studies that consider the contextual factors take into account work conditions, initial placement, administrative support, school facilities or school achievements to determine their contribution to faculty members’ burnout (Kelly & Northrop, ). Thus, it is considered that the decision to retire is at least partly influenced by the environment where an individual worker operates.…”
Section: Background Of the Studymentioning
confidence: 99%
“…There is a strong influence on the decision to retire from the work attitudes of the worker; those he or she possesses towards retirement and the norms at the workplace (including perceived social pressure for retirement). Studies that consider the contextual factors take into account work conditions, initial placement, administrative support, school facilities or school achievements to determine their contribution to faculty members’ burnout (Kelly & Northrop, ). Thus, it is considered that the decision to retire is at least partly influenced by the environment where an individual worker operates.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Many researchers and employers are interested in factors influencing teacher job satisfaction and teacher decisions to enter or leave the profession (Mansfield, Wosnitza, & Beltman, 2012;Sinclair, Dowson, & McInerney, 2006). Teacher turnover, particularly at the beginning of their career, is mostly associated with low salary, lack of administrative support, low decision-making power and autonomy, unsatisfactory societal status, discordance between personal and school values, and disruptive student behavior (Bentea & Anghelache, 2012;Borman & Dowling, 2008;Ingersoll, 2001;Kelly & Northrop, 2015;Kersaint, Lewis, Potter, & Meisels, 2007;Skaalvik & Skaalvik, 2011;You & Conley, 2015). These findings emphasize the importance of researching factors associated with teacher motivation to enter and remain in the teaching profession.…”
Section: Highlightsmentioning
confidence: 99%
“…We believe that there is potential for counseling and educational interventions that aim to enhance pre-service and in-service teachers' optimism and career engagement. Similarly, Kelly and Northrop (2015) suggested that counseling for career goals may have a positive effect on beginning teachers' career satisfaction. Experimental or longitudinal research into such interventions may provide evidence to test their impact and outcomes.…”
Section: Implications For Teacher Education and Teaching Practicementioning
confidence: 99%
“…Such research is important because the workforce of school teachers is demonstrably in crisis with high levels of attrition among teachers who do not adjust to the demands of the occupation (OECD, 2013). A focus on teachers' qualities is present in recent calls in the USA for selecting the so-called best and brightest from highly selective colleges into teacher degree programs (Kelly & Northrop, 2015). Despite the putative benefits of such selectivity, the results of Kelly's and Northrop's (2015) longitudinal study highlight the importance of maintaining teachers' career satisfaction in the early years of practice so as to guard against exit from the profession.…”
mentioning
confidence: 98%
See 1 more Smart Citation